Observation of Negative Magnetic Hysteresis Loop in ZnO Thin Films - Micah Haseman; Pooneh Saadatkia; David Winarski; Armando Hernandez; Matt Kusz; Wolfgang Anwand; Andreas Wagner; Sunil Thapa; A. M. Colosimo; Farida A. Selim (Journal of Spectroscopy)
We report on the observation of an unusual negative magnetic hysteresis loop in ZnO thin film codoped with cobalt and aluminum (Co-Al:ZnO), while other transition-metal-doped ZnO films, such as Cu-doped ZnO and Mn-doped ZnO, exhibit normal hysteresis loops. The unusual magnetic behavior is ascribed to the presence of double magnetic layers with different magnetic moments due to the change of structural defects across the film layers. Positron annihilation measurements confirmed the presence of unique microstructural changes in the Co-Al:ZnO film. This study shows that defects in diluted magnetic semiconductors may induce not only ferromagnetism but also novel magnetic behaviors.